2022
DOI: 10.1002/hbm.25970
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric functional segregation facilitates target detection during sustained visuospatial attention

Abstract: Visuospatial attention is strongly lateralized, with the right hemisphere commonly exhibiting stronger activation and connectivity patterns than the left hemisphere during attentive processes. However, whether such asymmetry influences inter‐hemispheric information transfer and behavioral performance is not known. Here we used a region of interest (ROI) and network‐based approach to determine steady‐state fMRI functional connectivity (FC) in the whole cerebral cortex during a leftward/rightward covert visuospa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…There is evidence of enhanced intrahemispheric functional connectivity of AN in the right hemisphere in BD patients [12,[54][55][56], accompanied by similar findings in structural connectivity [57,58]. The AN in the right hemisphere tends to play an important role in spatial attention and executive control, which may reflect a compensatory mechanism for related functions [59][60][61]. We found that the triggers of MLI changes were different in the AN of the bilateral hemispheres, and some studies [62,63] have pointed out the asymmetry of the AN itself.…”
Section: The Increased MLI Of An In the Right Hemisphere Is Caused By...mentioning
confidence: 81%
“…There is evidence of enhanced intrahemispheric functional connectivity of AN in the right hemisphere in BD patients [12,[54][55][56], accompanied by similar findings in structural connectivity [57,58]. The AN in the right hemisphere tends to play an important role in spatial attention and executive control, which may reflect a compensatory mechanism for related functions [59][60][61]. We found that the triggers of MLI changes were different in the AN of the bilateral hemispheres, and some studies [62,63] have pointed out the asymmetry of the AN itself.…”
Section: The Increased MLI Of An In the Right Hemisphere Is Caused By...mentioning
confidence: 81%
“…The literature suggests that drawing asymmetries, which can be a manifestation of attentional and directional biases, are a consequence of a complex interaction between biological, motoric, and cultural factors (DiNuzzo et al, 2022;. The asymmetries observed in graphomotor productions such as drawing may reflect the implication of cerebral lateralization (i.e., right hemisphere dominance for visuospatial attention), biomechanical (i.e., the ease for outward oriented motor movements) and cultural factors (i.e., script directionality).…”
Section: Discussionmentioning
confidence: 99%